PENGEMBANGAN MODUL EKOSISTEM BERBASIS GUIDED DISCOVERY LEARNING SISWA KELAS VII SMP NEGERI 1 AMANDRAYA - Laia, Puspa Mega (TUNAS : Jurnal Pendidikan Biologi, 2024)
This research aims to produce products based on guided discovery learning on Ecosystem material that are valid, practical and effective. The type of development in this research is the development of a 4-D model, namely defining, designing, developing and disseminating. The research method used in this research is research and development. Based on the results of distributing questionnaires to students, it was found that the guided discovery learning-based module that was tested was very valid, very practical and very effective. The test results of the three module validators obtained very valid values ​​with the average number of the four variables being 90.88. As a result of the teacher’s practicality of the module, an average score of 3.85 was obtained in the very practical category. The results of the student motivation questionnaire test were categorized as very high with a score of 89.22. And student learning outcomes in the cognitive domain show very good results with an average score of 82.61. So, through these results, it can be concluded that the development of modules based on guided discovery learning on ecosystem material can be declared valid, practical and effective in supporting student learning outcomes. Based on the results of this research, it is recommended to (1) Teachers. Science (Biology) subject teachers should be able to use learning modules based on Guided Discovery Learning as teaching materials in the learning process because they can facilitate the teaching and learning process activities, (2) Students. Through this teaching material, it is hoped that students can broaden their horizons regarding learning science (biology) on Ecosystem material, (3) For future researchers, this guided discovery learning-based module can be used as reference material in subsequent relevant research